Pengaruh Green Accounting, Corporate Social Responsibility (CSR), dan Struktur Modal Terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Sektor Energi di Bursa Efek Indonesia Tahun 2018 – 2022) - Oktiara, Karin; Effriyanti, Effriyanti (CV. Rayyan Dwi Bharata, 2024)
This study aims to analyze the effect of green accounting, corporate social responsibility (CSR), and capital structure on firm value. This type of research is quantitative research with an associative approach. The population in this study are energy sector companies listed on the Indonesia Stock Exchange in 2018-2022. The sample selection method used in this study was purposive sampling. Hypothesis testing is done using panel data regression with Eviews version 12 tools. The results showed that simultaneously green accounting, corporate social responsibility (CSR), and capital structure variables have an influence on firm value. While partially green accounting and corporate social responsibility (CSR) have no influence on firm value. While capital structure has an influence on firm value.